Semarang Young People's Perception of News in Online Media Suaramerdeka.com - Sukma, Pascalia Prasasti; Harnita, Pratiwi Cristin; Krisnwati, Ester (Sahabat Publikasi, 2024)
The aim of this study is to investigate the differences in perceptions among readers regarding news on the online media suaramerdeka.com, as well as how young people in Semarang perceive themselves after reading the news as a source of information. This research employs a qualitative research approach with an explanatory, descriptive nature within a phenomenological paradigm. The study utilizes descriptive qualitative research methods focused on answering research questions. The findings indicate that suaramerdeka.com is considered an easily understandable information source due to its straightforward news content. The perceptions of young people in Semarang regarding news on suaramerdeka.com show that they often read news through online portals and are aware of suaramerdeka.com's existence. The study includes interviews with five sources and 30 respondents who mentioned that suaramerdeka.com is one of the largest media outlets in Central Java. After reading news on suaramerdeka.com, respondents found it easier to understand due to its straightforward content. Thus, it can be concluded that their perceptions are influenced by their previous experiences.